1990
DOI: 10.1257/jep.4.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Line-Item Veto: Where Is Thy Sting?

Abstract: P roponents of giving the president the authority to use a line-item veto argue that the institutional change is needed to limit special-interest legislation and restrain spending. Opponents respond that it would grant too much added power to the president, thereby upsetting the delicate balance wisely crafted by the founding fathers. This article focuses on the presumption, evidently shared by both sides in the debate, that adoption of item-veto authority will have significant consequences in terms of budget … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Most studies have found little evidence for its importance in influencing total spending (e.g. Carter and Schap, 1990;Holtz-Eakin, 1988;Nice, 1988). See Masia (1995), though, for an argument that the composition of spending may be affected by this institution.…”
Section: Actors and Preferencesmentioning
confidence: 99%
“…Most studies have found little evidence for its importance in influencing total spending (e.g. Carter and Schap, 1990;Holtz-Eakin, 1988;Nice, 1988). See Masia (1995), though, for an argument that the composition of spending may be affected by this institution.…”
Section: Actors and Preferencesmentioning
confidence: 99%
“…In many states, the governor possesses some version of line-item veto authority (Advisory Commission on Intergovernmental Relations, 1991). Carter and Schap (1990) argue that in many circumstances the effect of a line-item veto on aggregate spending is indeterminate, because the line-item veto alters the composition rather than the aggregate level of spending. That is, the reduction in expenditure on one line item may be more or less than offset by changes in expenditure on another line item.…”
mentioning
confidence: 99%
“…Several multistate studies employing econometric models have analyzed the impact of the item veto, compared with the full executive veto, on the level and composition of state spending. In general, those studies found that in the long‐term state budgets are not altered by the item veto, and that the short‐term impact of the item veto depends upon the political party of the governor and the party composition of the legislature (Abrams and Dougan ; Alm and Evers ; Carter and Schap ; Dearden and Husted , ; Holtz‐Eakin ; Indridason ; Nice ).…”
Section: Literature Reviewmentioning
confidence: 99%